Pengaruh Kombinasi Silika dan Asam Humat terhadap Ketersediaan Nitrogen dan Pertumbuhan Tanaman Padi pada Tanah Berpasir (Soilrens, 2021)
Sandy soils commonly have high macropores and low plant nutrient availability. This condition is caused by the soil matrix which has almost no negative charge, so there's no strong adsorption capacity for ions.  The next impact is that nutrients become easily lost because they're washed or evaporated. Nitrogen loss has been reported to reduce rice production by 6.10%. The research objective was to examine the effective application of humic acid and silica to improve the availability of nitrogen nutrients in sandy soil. Humic acid from compost and silica from husk charcoal is expected to increase the negative charge of the soil (cation exchange capacity) so that can adsorb and fixate nutrient ions such as nitrogen. The research was carried out from March 2021 to September 2021 in the greenhouse and land resource laboratory of the Faculty of Agriculture, National Development University "Veteran" East Java. The research was structured using a factorial Completely Randomized Design (CRD). The first factor is silica dose with a level of 0 ton ha-1, 0.5 ton ha-1, 1 ton ha-1, and 1.5 ton ha-1.  The second factor is the dose of humic acid with a level of 0 kg ha-1, 20 kg ha-1, 40 kg ha-1, and 60 kg ha-1.  Observation parameters include the availability of N in the soil, the growth of rice plants which include plant length and the number of tillers. The results showed that the combination of humic acid and silica didn't significantly affect plant length and number of tillers, but had a significant effect on nitrogen availability to plant. The best dose of the combination of silica with humic acid on nitrogen availability in sandy soils is S3H1 (Silica 1.5 ton/ha with humic acid 20 k.ha-1).